Our Messengers Say - Harun Yahya, author 323805 (New Delhi : Goodword Books, 2004)
OUR MESSENGERS SAY : The lives and struggles of the messengers are abundant in lessons for believers who think and are inclined to learn from them. This book examines how some of Allah's messengers communicated Allah's message to the communities to which they were sent. The purpose is to remind readers of the moral excellence of these honourable messengers of Allah, and of the sincerity, effort and commitment they displayed in spreading the message, to refresh our respect and love for them and call attention to the importance of the issues they conveyed. Moreover, by remembering what these messengers communicated to their peoples, we are inclined to reconsider our deficiencies and errors and to atone for them. The life stories of the prophets furnish us today-as much as they did the people who lived in those times-with lessons in faith. In the future too, they will remain a source of guidance. This book calls for believers to see the divine purpose in the stories of the messengers, to ponder over them and to embrace them.